Pain Perception and Anesthesia Requirements in Diode Laser vs. Traditional Methods for Second Stage Implant Exposure - Jameel, Saad M.; Alkurtas, Salah A.; Dhahir, Mohammed K. (Iraqi Journal of Physics, 2024)
Using a 940nm diode laser or traditional methods, second-stage implant exposure involves removing soft tissue above the dental implant to expose the implant fixture and complete the implant procedure. This study included twenty-three patients (43.5% of whom were males, and the female percentage was 56.5%), aged between 18 and 70 years, who had at least two implants (3-6 months after implant insertion). Implant exposure was performed in case 1, using the traditional methods of puncture, flap, or incision, and in case 2, using a 940 nm diode laser. The study took place in Baghdad, Iraq. The results showed that the average pain in the laser group was 1.48, which was less than the average pain in the traditional group, which was 3.70. The pain scores that patients immediately reported for the laser cases were between 0 and 3, while the pain scores for the conventional cases were higher, ranging from 2 to 6. This was statistically significant in favour of the laser cases. All patients using the traditional method required infiltration anaesthesia, while 20 patients were satisfied with topical anaesthesia in the diode laser cases; this was statistically significant, favouring the laser method. This study revealed that the 940 nm diode laser is more efficient than the conventional method regarding the patient's perception of pain and the need for infiltration anaesthesia.